Security-Aware Design for Cyber-Physical Systems A Platform-Based Approach - Lin, Chung-Wei.; Sangiovanni-Vincentelli, Alberto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Addressing the rising security issues during the design stages of cyber-physical systems, this book develops a systematic approach to address security at early design stages together with all other design constraints. Cyber-attacks become more threatening as systems are becoming more connected with the surrounding environment, infrastructures, and other systems. Security mechanisms can be designed to protect against attacks and meet security requirements, but there are many challenges of applying security mechanisms to cyber-physical systems including open environments, limited resources, strict timing requirements, and large number of devices.  Designed for researchers and professionals, this book is valuable for individuals working in network systems, security mechanisms, and system design. It is also suitable for advanced-level students of computer science. .
Introduction -- Security Threats in Cyber-Physical Systems -- Security Mechanisms for CAN Protocol -- Security-Aware Mapping for CAN-Based Systems -- Security-Aware Mapping for TDMA-Based Systems -- Security-Aware Design for V2V Communication -- FSM-Based Security-Aware Design -- Graph-Based Security-Aware Design -- Conclusions.
Keywords: Electronic circuits; Data protection; Computer networks .; Electronic Circuits and Systems; Data and Information Security; Computer Communication Networks